The Behavior of Different Precast Concrete Structures Under Seismic Action. (2016) - Tosa, Florin V.; Salha, Riyadh
Abstract: The paper aims to establish the differences of stiffness between five types of precast concrete structures. Based on that, the results will be analysed to present the seismic areas where the proposed types of structures can be applied. Therefore, we are going to use a simplified method to compare between those five types, based on the empirical principle that refers to the rigidity of frameworks that form the structure. In this way, the approach for structural design methods will be able to be optimized at an early stage of the project methods. Thus, to validate the results and set the behaviour of the structures, we will rely on two well-known types of structures "frames and walls solutions" which are already used in precast concrete industry. However, in the near future, and starting from this topic we will analyse some details for precast elements connection, such as frames connection or joints between walls.